Helicobacter pylori prevalence, histological and antibiotic resistance patterns among paediatric patients, at a single hospital in Lisbon, during a 5- year period - Santos, A. (2016)
Background : Decreasing prevalence of H. pylori infection has been reported worldwide, in parallel with the improvement in sociodemographic conditions. In contrast, in Portugal, there is still a high prevalence of infection, including in pediatric population, and of gastric carcinoma. Aim : This study aims to evaluate H. pylori prevalence, histological and antibiotic resistance patterns in symptomatic Portuguese children/adolescents attending a hospital in Lisbon.